Higher-Order Executive Function in Middle School: Training Teachers to Enhance Cognition in Young Adolescents - Gamino, Jacquelyn F.; Frost, Courtney; Riddle, Russell; Koslovsky, Janet; Chapman, Sandra B. (Frontiers in Psychology, 2022)
The epoch of adolescent brain development is an ideal time to train complex thinking skills, and middle schools provide an ideal environment to train and foster this acquisition. Unfortunately, few teachers are equipped with enough knowledge of the science of learning and evidence-based methodology, to ensure all students are given sufficient opportunity to develop their cognitive capacity to the fullest. Using our evidenced-based higher-order executive function training program, we trained current teachers to provide cognitive training to their students. The results of this study demonstrate the efficacy of teacher-implemented intervention for immediate improvement in high-level executive function capacities such as gist-reasoning and interpretive statement production. More importantly, we found evidence of far transfer via students’ improved academic performance in all standardized test content areas (Reading, Mathematics, Science and Social Studies) when compared to their untrained peers. Our findings support the importance of providing intensive professional development that afford educators with a greater understanding of the brain, how we learn, and the importance of evidence-based programs to advance and instill high-level executive function in all students.